Popular Culture as Historical Document: The Portrayal of American History in the John Adams Miniseries - Holiš, Viktor (Univerzita Pardubice, 2025)
This Bachelor Thesis focuses on the depiction of American history in a TV miniseries John Adams. The theoretical parts of this thesis focus on defining terms and concepts, such as The Founding Fathers, Federalist and Democratic-Republic parties, and how popular culture takes part in teaching history. The practical part of this thesis then works with the concepts defined in the theoretical part and analyses the depiction of John Adams and other representatives portrayed in the miniseries.
Populární kultura jako historický dokument: zobrazení americké historie v televizní minisérii John Adams
Keywords: John Adams; Otci zakladatelé; Federalistická strana; strana Demokratických Republikánů; Hollywoodský historik; John Adams; The Founding Fathers; The Federalist Party; The Democratic-Republican Party; Hollywood historian